Understanding the efficacy of electron and hole transport layers in realizing efficient chromium doped BiFeO3 ferroelectric photovoltaic devices. (1st September 2020) - Renuka, H.; Joshna, P.; Venkataraman, B. Harihara; Ramaswamy, Kannan; Kundu, Souvik
Graphical abstract: Highlights: Pt/BFCrO/WS2 /ITO, Pt/NiO/BFCrO/ITO, and Pt/NiO/BFCrO/WS2 /ITO ferroelectric photovoltaic devices were fabricated. The Pt/NiO/BFCrO/WS2 /ITO device demonstrated much better performance as compared to the other two devices. The band-diagram was proposed and the electrical results were correlated with the band-diagram. Sulfur passivation of WS2 greatly enhanced the carrier injection in the p-i-n device through the electron transport layer. The performances were further improved in sulfur passivated p-i-n devices as compared to the unpassivated one. Abstract: In this work, we report the fabrication of Pt/ i-n /ITO, Pt/ p-i /ITO, and Pt/ p–i–n /ITO heterojunction photovoltaic (PV) devices, where i is the lead-free 2% Cr doped BiFeO3 (BFCrO) ferroelectric, n is the WS2 electron transport layer (ETL), p is the NiO hole transport layer (HTL), and Pt and ITO are the top and bottom electrodes, respectively. In the tandem structure, the materials bandgaps were increased from anode to cathode side; hence the device could absorb the maximum solar light. The electrical performance parameters were compared for all the above-mentioned devices. The p-i-n device yielded an open-circuit voltage (VOC ) and a short-circuit current density (JSC ) of 0.60 V and 0.76 mA·cm −2, respectively, which leads to the improvement in an efficiency of about 70% as compared to the other two heterojunctions. The two depletion regions formed in the p-i-n heterostructure provide the necessary force to drive the carrier separation, which was confirmed through the electrochemical impedance spectroscopy. A band-diagram has been projected to understand the device operation mechanism. To reduce the structural defects in WS2 and further improve the PV performance parameters in p-i-n devices, sulfur passivation has been performed on the WS2 films. This process offered significant carrier extraction properties than the unpassivated one. The electrical performances for both the passivated and unpassivated devices were compared to elucidate the impact of sulfur passivation. Surprisingly, both the VOC and JSC were improved in the passivated devices, and the efficiency was remarkably increased to an additional 70% as compared to the unpassivated one.